Of Monsters and Men: The Aesthetics of the Alt-Right - Jungen , Thari (Stan Rzeczy, 2019)
In February 2016, the Institute for Falsification researched the production of fake news in Veles, North Macedonia. Focusing on a specific hoax distributed from Veles via social media, this article analyses the political and aesthetic effects of fake news. It argues that fakes and hoaxes (mis)use established references to renew pre-existing discourses, media techniques, and symbols. The present definition of fakes is therefore insufficient for these practices.